BLOCKCHAIN AND MARKETING: TRANSPARENCY AND TRUST IN THE DIGITAL AGE - Nenden Hendayani; Euis Eka Pramiarsih; Yusnaini (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Blockchain has become one of the technological innovations that has had an impact on the world of marketing, particularly in terms of transparency and building trust in the digital age. This technology enables the recording of data or transactions that cannot be altered, thereby creating a more open and accountable system. In the context of marketing, blockchain helps brands to be more honest, while also giving consumers control over their personal data.